Analisis Komposisi Kimia Daun Kelakai (Stenochlaena palustris Bedd.) dengan Berbagai Pelarut menggunakan GCMS (Chemical Composition Analysis of Stenochlaena palustris Bedd. Leaves using Various Solvents on GCMS) - Nurmilatina, Nurmilatina (Kementerian Perindustrian, 2017)
The selection of suitable solvents is essential for extracting the desired compounds from plant cells. GCMS is an instrument that can be used to identify such compounds. Therefore, this study objective is to extract kelakai leaves using various solvents and analyze the composition of chemical compounds using GCMS instrument. Kelakai leaves was extracted using three solvent variations: a1 = aquadest, a2 = ethanol, and a3 = ethanol 50%; and the maceration time variations: b1 = 1 day, b2 = 2 days, and b3 = 3 days. The best extraction method was aquadest as solvent and one day maceration. The chemical compound extracted were phenolic, alkaloids and terpenoids, such as 2,5-bis [(trimethylsilyl) oxy] benzaldehyde 1,86%, linalool 1,28%, phenethyl alcohol 3,55% and 7-chloro-5-phenyl-1-(trimethylsilyl)-1,3-dihydro-2H-1,4-benzodiazepines-2-on 1,16 % db.Keywords: composition analysis, GCMS, maceration, Stenochlaena palustris Bedd.